银屑病患者的述情障碍逆转. (4th February 2019) - Sampogna, F.; Puig, L.; Spuls, P.; Girolomoni, G.; Radtke, M.A.; Kirby, B.; Brunori, M.; Bergmans, P.; Smirnov, P.; Rundle, J.; Castiglia, A.; Lavie, F.; et al.
Abstract : Linked Article:  Sampogna et al. Br J Dermatol 2019;180 :397–403